(untitled) (Global Journal of Medical Research, 2013)
Objective : To compare different nasal cavity nursing methods on mechanically ventilated patients. Methodology : According to acute physiology and chronic health evaluation (APACHEII), 615 cases of mechanically ventilated patients were divided into group A, group B and group C by stratified random method. Traditional oral nursing plus a secretions from oral cavity and nasal cavity q6h were done in group A. Based on methods in group A, normal saline was used for cleaning nasal cavity in group B. Besides the methods in group A, atomizing nasal cleansing a6h was also used in group C. Incidence rate of Ventilator- Associated Pneumonia (VAP) and APACHE II scores after administrating were compared. The correlation between APACHE II score and outcomes was analyzed by Spearmanrank correlation. Results : In group A, incidence of VAP was 36.76%, group B was 30.24%, group C was 20.38%, and the difference was statistically significant. APACHE II scores in group C were significantly lower compared with group A and B. APACHE II score was negatively correlated with clinical outcomes. Conclusions : For mechanically ventilated patients, nasal nursing can’t be ignored and the new atomizing nasal cleaning is an effective method for VAP prevention.